A A review of bioactive compounds produced by endophytic fungi associated with medicinal plants - Soares, Deyze Alencar; Rosa, Luiz Henrique; da Silva, Juliana Fonseca Moreira; Pimenta, Raphael Sanzio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
Interest in exploring endophytic fungi has increased in recent years, especially those associated with medicinal plants, reflecting the great potential of these microorganisms for the production of bioactive substances. Medicinal plants shelter a high diversity of endophytes that represent targets for use in biotechnological processes. These fungi synthetize several compounds that can be used in pharmaceutical, agricultural and other industries. Additionally, endophytes produce many bioactive metabolites involved in host-endophyte symbiosis, such as those that increase resistance to stressful conditions, alter physiological properties, and produce phytohormones, toxins, antimicrobial compounds and medicinal substances, immunosuppressants, antitumoral agents, and other biotechnological substances of interest, such as enzymes. In this review, information regarding plant interactions with endophytes is highlighted, contributing to a better understanding of this association, benefits and potential for biotechnological utilization.
Keywords: Host-endophyte interaction; Secondary metabolites; Bioactive compounds